Tourism and ICTs: Advances in Data Science, Artificial Intelligence and Sustainability c - Guevara Plaza, Antonio J.; Cerezo Medina, Alfonso; Navarro Jurado, Enrique; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open-access book presents the best research papers from the XIV International Congress on Tourism and Information and Communications Technologies (TURITEC2023), held in Málaga, Spain from 19 to 20 October 2023. The book explores the profound impact of COVID-19 on the tourism industry and the increasing importance of digitalization and Information and Communication Technologies (ICTs) as key drivers for the industry's recovery, alongside sustainability. This curated collection of research papers offers conceptualizations, methodologies, analyses, and empirical case studies that illuminate the path to a resilient and sustainable future for tourism.
Data science: digitalization, mobility and user-generated content (UGC) -- Artificial intelligence and tourism -- Sustainability, platform economies and new realities.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Tourism; Management; Artificial intelligence; Business information services; Tourism Management; Artificial Intelligence; IT in Business